SIMULATION OPEN CHANNEL FLOW FOR VARIOUS FROUDE NUMBER - Huda N A, Nurul
Flow over a bump occurs when the water flow with specific velocity in a wide channel approaches a bump, so that the flow will be deformed. In this research, we study free surface deformation due to flow over a bump. We investigate this phenomena using non-dispersive SWE model and dispersive Boussinesq model. Using (the non-dispersive) SWE model, three types of flow are simulated. Steady free surface for the case of subcritical flow, supercritical flow and frictionless ow are nicely comparable with analytical predictions. Next, the Boussinesq model is solved using finite difference methods with predictorcorrector step. In Boussinesq simulation, we observe the appearance of undulation in dam break flow test. This undulation is expected to appear in dispersive scheme the Boussinesq numerical scheme is implemented to recompute free surface flow oaver a bump. Various interesting profles are produced.